Reflections of science students on their experience of an academic development programme in South Africa - Potgieter, Marietjie; Harding, Ansie; Kritzinger, Quenton; Somo, Charity; Engelbrecht, Johann (South African Journal of Higher Education, 2016)
This study reports on student experiences in an access programme in the science faculty at the University of Pretoria, South Africa, named the BSc Four Year Programme (BFYP). The programme has a preparatory 18 months phase after which students join the mainstream programme. The aim of the paper is to give a voice to students who enrolled in 2008 and are either still in the system or have successfully completed the degree programme. We identify three performance bands – good, moderate and poor performers, and focus on their experiences in the preparatory phase of the BFYP, reporting on personal perceptions of the structure of the programme, on challenges faced and on preparedness upon transition to the mainstream programme. The distinguishing feature of the paper is that experiences are reported on through the lens of the different performance bands, adding shades of intensity to the different perspectives. Whilst the structure and features of the BFYP were experienced positively by most students across the performance bands the voice of the poor performing students emerged in this study, expressing their sense of frustration, their inability to cope and their failure to identify their challenges and to seek assistance. The need to equip under-performing students more effectively in terms of academic and life skills is the key finding of this work and should be of interest to the wider audience of educators and counsellors involved in access programmes.